Ein Beitrag zur Morphologie und Biologie von Philygria spp. (Diptera, Ephydridae). - Froese, Axel (Contributions to Entomology = Beiträge zur Entomologie, 1993)
The immature stages of Philygria spp. have been described on the basis of microscopical drawings and REM-photos. The evolution cycle of Philygria spp. is given with the help of phenological data of all developmental stages. In 1988/1989 and 1989/1990 the apparent mortality was calculated with 88,3% and 90,9% respectively.